Application of Jaccard Distance Measure for IVIF MCDM Problems - Vulimiri, Anusha; Veeramachaneni, Sireesha (IndoMS, 2021)
This paper proposes an approach to solve Multiple Criteria Decision-making (MCDM) problems when the data given by expert is Interval-Valued Intuitionistic Fuzzy (IVIF) information. A decision-making model is constructed by using the distance measure: Normalized Jaccard distance measure. The robustness of the model is illustrated and validated through numerical example. Further, the problem of choosing best e-learning tool in higher education is considered as a case study.